(untitled) (Palíndromo, 2023)
The Grotesque has its place in aesthetic categories. This place intensified when artists moved away from the idea of Beauty as a traditional and hegemonic reference of Visual Art and started to produce works that assumed positions that were intentionally contrary to the traditional conception of Idealized Beauty, investing in Ugliness as an oppositional or expressive attitude, especially from the moment when experimental and contestatory propositions were adopted on the way to Modernism. The dichotomous opposition between Beautiful and Ugly made possible the unfolding of the Grotesque to the extent that it, the Grotesque, when emerging from ugliness, led some artists to resort to the use of dense, intense and even aggressive forms in an aesthetic segment that began to thematize scatological, morbid and grotesque aspects. This is the reason that led to the development of this work whose objective is to explain the relations between the atavism that involves human relations with death and morbidity using photographic images and the approach with discursive semiotics to reflect on the Grotesque from a core fundamental opposition: Beauty versus Ugliness or the Grotesque as a methodological strategy for analyzing the production of meaning.